Armenia Takes on Water Management Challenges : Public-Private Partnerships in Water Sector - Tokhmakhian, Zaruhi (World Bank, Washington, DC, 2014)
For many years after the collapse of the Soviet economy, most of the water supply and sanitation systems in Armenia were in disrepair. The country was faced with increasing demand, deteriorating assets and dilapidated infrastructure, which resulted in a steadily decreasing and costly provision of services. Despite an abundance of water in the country, for almost all Armenians, water was available for only a few hours a day. In recent years, Armenia has made significant strides in reforming the water sector by developing policies, enacting laws, and drawing up plans, programs and strategies aimed at improving water service provision. This report presents a background to the water and wastewater sector in Armenia and summarizes the strategy that the Government of Armenia took to meet the challenges faced by the sector through the effective and pragmatic use of different modalities of Public-Private Partnerships (PPP). Section 2 of this report analyzes the successes and challenges to date, as well as evaluates against some key criteria, progress by each of the three types of PPP used in the country. Section 3 summarizes some of the key lessons learned. Section 4 discusses possible future PPPs in the water sector.